Hydrothermal alkaline treatment for efficient degradation of per- and polyfluoroalkyl substances - ZHANG Qiang; PENG Yuhua; ZHANG Jing; MA Jun (Gongye shui chuli)
Per- and polyfluoroalkyl substances(PFAS) are persistent organic pollutants that are chemically stable and difficult to degrade. These compounds can be detected in environmental media, such as water and soil, and have the potential to accumulate in the human body through the food chain, posing risks to reproductive and immune systems. Consequently, efficient PFAS degradation has gained widespread attention. Hydrothermal alkaline treatment (HALT) utilizes subcritical water (170-350 ℃,2-22 MPa) under strongly alkaline conditions to generate hydroxyl radicals (·OH). These radicals attack the carboxyl or sulfonic groups in PFAS to facilitate decarboxylation or desulfonation, hydrolytic defluorination, and rapid complete degradation. HALT represents an efficient, low-energy, and cost-effective technique for PFAS treatment. This paper summarized effects of HALT on PFAS degradation and defluorination, explored the influence of reaction conditions (such as alkali concentration, temperature, catalysts, and environmental matrices), and elucidated the decarboxylation-hydroxylation-elimination-hydrolysis pathway. Additionally, the practical engineering outcomes of HALT in treating aqueous film-forming foam wastewater, remediating PFAS-contaminated soil and water bodies, regenerating PFAS-saturated activated carbon, and processing Typha latifolia with accumulated PFAS were reviewed. Lastly, the paper anticipated future research directions for HALT, aiming to provide theoretical guidance and technical references to advance the development of HALT dealing with PFAS.